1991
DOI: 10.1177/39.10.1940305
|View full text |Cite
|
Sign up to set email alerts
|

A temporal and ultrastructural relationship between heparan sulfate proteoglycans and AA amyloid in experimental amyloidosis.

Abstract: Previous histochemical studies have suggested a close temporal relationship between the deposition of highly sulfated glycosaminoglycans (GAGs) and amyloid during experimental AA amyloidosis. In the present investigation, we extended these initial observations by using specific immunocytochemical probes to analyze the temporal and ultrastructural relationship between heparan sulfate proteoglycan (HSPG) accumulation and amyloid deposition in a mouse model of AA amyloidosis. Antibodies against the basement membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(69 citation statements)
references
References 24 publications
4
63
0
2
Order By: Relevance
“…Glycosaminoglycans (GAGs), in particular heparin/heparan sulfate (HS), are known to associate with AA amyloidosis (21,22). Previous studies showed that the binding of mouse SAA to HS depends primarily on charge interactions, and that the association promotes the HDL release of SAA and facilitates their aggregation (23)(24)(25).…”
Section: Resultsmentioning
confidence: 99%
“…Glycosaminoglycans (GAGs), in particular heparin/heparan sulfate (HS), are known to associate with AA amyloidosis (21,22). Previous studies showed that the binding of mouse SAA to HS depends primarily on charge interactions, and that the association promotes the HDL release of SAA and facilitates their aggregation (23)(24)(25).…”
Section: Resultsmentioning
confidence: 99%
“…Purified RNA was separated on 1.2% agarose gels containing 2.2 M formaldehyde as previously described [24]. The RNA was then hybridized overnight at 42ЊC with [a 32 P]-dCTP-(Amersham, Oakville, Ontario, Canada) labelled probes using a nick translation system (GIBCO/BRL). A tumour necrosis factor-a (TNF-a) cDNA probe (1.3 kb) was kindly provided by Dr A. Cerami (Rockefeller University, NY, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, SDS-PAGE analysis of culture medium did not show any appearance of the 8 kDa protein band which would further suggest that AA fibrils were not formed. Other components present in vivo, such as the different common elements found in several types of amyloid deposits (serum amyloid P, heparan sulphate proteoglycan, Apo-E) [30][31][32][33][34][35], may be required for inducing a partial degradation and/or fibril formation. These common elements may be relevant to test in vitro to determine whether they play a role in the initiation phase of fibril formation.…”
Section: Saa Degradation By Macrophage Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure causes amyloid formation in affected organs within 24 h (7). Experiments with this model have revealed an intimate structural and temporal relationship between AA amyloidosis and heparan sulfate (HS) (8), a sulfated polysaccharide expressed on the cell surfaces and in the extracellular matrix, suggesting a role for HS in SAA amyloidogenesis. Further, cell surface HS converts HDL-associated SAA into AA amyloid fibrils in cell culture, a process that can be inhibited by a C-terminal SAA peptide selectively binding to HS (9).…”
mentioning
confidence: 99%